Experience with abatacept used in the treatment of patients with rheumatoid arthritis - V I Mazurov; Sergei Vladimirovich Dolgikh; E S Zhugrova; Yu B Shulman; R R Samigullina (Научно-практическая ревматология, 2011)
The efficiency and safety of therapy with abatacept in combination with methotrexate were studied in patients with rheumatoid arthritis. The performed therapy was shown to reduce the activity of an immune inflammatory process and the magnitude of articular syndrome and to improve the patients' functional status.